THE SPECIFICS OF IMPLEMENTING THE EXIT TAX IN UKRAINE UNDER MARTIAL LAW - Zolkover Andrii О.; Kovalenko Dmitry І. (Journal of Strategic Economic Research, 2023)
This study attempts to identify effective pathways to boost business activity, in particular through implementing the exit tax policy. It is observed that with Russia’s launching a full-scale invasion to Ukraine, almost all economic processes slowed down, most of businesses in the areas of hostilities were forced to either suspend their activities or close. However, the government is investing much efforts to support entrepreneurs through the adoption of a number of laws that will help businessmen gradually return to their normal functioning, in the field of taxation, too. It is argued that in modern realia of martial law, the issue of introducing exit tax is gaining more relevance, since in the future it will contribute to multiplying long-term economic benefits for the national economy. It is emphasized that the exit tax which is also called a corporate tax might enhance further strategic areas of more efficient use of company profits offering better opportunities for reinvesting and thus providing national producers with a strong impetus to develop and improve their performance in post-war economic recovery of Ukraine. From this perspective, a beneficial effect from implementing exit tax is that it will initiate de-offshore mechanisms and prevent such anti-tax avoidance planning strategies when business entities wilfully overstate their expenses in order to optimize the tax burden. The research findings demonstrate that before February 24, 2022, issues of implementing exit tax in Ukraine had been the most controversial debate topic. The last attempt to introduce an exit tax assumed different timing of the adoption of project No. 3665, according to which the exit tax was supposed to come into effect on January 1, 2022 (provided that Draft Law No. 3665 would be adopted by July 15, 2021) and from January 1, 2023 (if Draft Law No. 3665 was adopted after July 15, 2021). The paper resumes that by Resolution No. 2035-IX of the Verkhovna Rada of Ukraine dated February 15, 2022, among the issues prepared for consideration at the plenary sessions, the following issues were also discussed: the Draft Law on Amendments to the Tax Code of Ukraine No. 1185 with regard to implementing an exit tax and the policies to combat the tax base erosion and profit shifting abroad and the Draft Law on Amendments to the Tax Code of Ukraine No. 3665 and No. 3665-1 and some other legislative acts of Ukraine as to implementing exit tax to replace the corporate income tax. The study also discusses the implications of the forecasts by the Ministry of Economy of Ukraine for 2022–2025, in particular, it is noted that if the exit tax is implemented in 2022, then starting from the second year, i.e. in 2023, Ukraine’s GDP will additionally increase by almost 1.1% with a further growth in 2025 to 3% due to synergy effects. Currently, the above draft laws No. 3665 and No. 3665-1 are being processed in the Parliament’s Committee.